Viologen‐Hypercrosslinked Ionic Porous Polymer Films as Active Layers for Electronic and Energy Storage Devices. Issue 10 (26th February 2018) - Wang, Luxin; Ding, Junjie; Sun, Sai; Zhang, Bin; Tian, Xiangyu; Zhu, Jinhui; Song, Sannian; Liu, Bo; Zhuang, Xiaodong; Chen, Yu
Abstract: Over the past decades, numerous scientists have focused on designing complicated monomers, developing new synthesis protocols, and optimizing chemical structures for realizing high‐performance organic or polymer electronics and energy storage devices. However, much less attention has been paid to ionic‐ and radical‐rich porous organic films, which are essential components of aforementioned devices. In this study, an air‐stable, large‐area, free‐standing, and viologen‐linked ionic porous polymer (denoted as IPP‐V) film is developed in situ through electrochemical polymerization. This film is applied to a device by sandwiching it between indium tin oxide (ITO) and Au (i.e., ITO/IPP‐V/Au); the device exhibits a memristive behavior with an ON–OFF current ratio of ≈2. After the IPP‐V film is subjected to thermal pyrolysis at 500 °C, the as‐produced film (denoted as IPP‐V‐500) acts as an active material for an in‐plane micro‐supercapacitor and exhibits a high volumetric capacitance level of up to 4.44 F cm −3 . This work not only offers a new and convenient strategy toward large‐area ionic porous polymer films for memristor, but also provides a new porous polymer derived carbon film for energy storage. Abstract : An ionic porous polymer film with air‐stable, large‐area, free‐standing, and viologen‐linked features is developed. Such film based sandwich‐like device exhibits typical memristive behavior. The in‐plane micro‐supercapacitor based on the thermal treated film exhibits ultrahigh volumetric capacitance. This work offers an easy strategy for fabricating ionic functional films toward high performance memory and energy storage devices.